2004
DOI: 10.4028/www.scientific.net/msf.467-470.129
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Primary Recrystallisation Microstructure of Cold Rolled and Annealed Fe 3% Si Single Crystals with Goss Orientation

Abstract: A silicon steel single crystal with {110}<001> Goss orientation was cold rolled up to 89 % thickness reduction and subsequently annealed. The evolution of the macroscopic cold rolling texture was investigated by x-ray diffraction. Local orientation relationships and the microstructure around and within Goss grains of deformed and annealed samples were analysed using the electron backscatter diffraction (EBSD) technique. During cold rolling a texture consisting of two strong {111}<112> components an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The relaxed constraints Tayor model, in which shear strains parallel to RD may occur, causes the formation of the {111}<112> orientation [67]. The {111}<112> rolling component is known to lead to the Goss orientation after Rex [66,68]. Dorner et al [68] attributed the transition from the {111}<112> deformation texture to the Goss Rex texture to the fact that the Taylor factor (2.4) of the Goss grains is lower than that (3.7) of the {111}<112> matrix.…”
Section: Evolution Of Goss Recrystallization Texture From {111}<112> mentioning
confidence: 99%
See 1 more Smart Citation
“…The relaxed constraints Tayor model, in which shear strains parallel to RD may occur, causes the formation of the {111}<112> orientation [67]. The {111}<112> rolling component is known to lead to the Goss orientation after Rex [66,68]. Dorner et al [68] attributed the transition from the {111}<112> deformation texture to the Goss Rex texture to the fact that the Taylor factor (2.4) of the Goss grains is lower than that (3.7) of the {111}<112> matrix.…”
Section: Evolution Of Goss Recrystallization Texture From {111}<112> mentioning
confidence: 99%
“…The {111}<112> rolling component is known to lead to the Goss orientation after Rex [66,68]. Dorner et al [68] attributed the transition from the {111}<112> deformation texture to the Goss Rex texture to the fact that the Taylor factor (2.4) of the Goss grains is lower than that (3.7) of the {111}<112> matrix. Dorner et al [69], in their study with 3.2% Si-steel single crystals, also found two types of Goss crystal volumes in 89 % cold-rolled specimen.…”
Section: Evolution Of Goss Recrystallization Texture From {111}<112> mentioning
confidence: 99%
“…In relation to this possibility, Park et al 11) observed that sub-boundaries exist exclusively in abnormally-growing Goss grains using transmission electron microscopy. Also, Dorner et al 12) confirmed the existence of sub-boundaries exclusively within Goss grains after primary recrystallization of a sheet sample reduced 89% by cold rolling of a single crystal of Goss orientation. The solid-state wetting mechanism could successfully explain many puzzling structures such as the formation of island and peninsular grains at the growth front 7,13) and the pancake-shaped growth of Goss grains in highly grain-oriented electrical steel of Fe3%Si.…”
Section: Introductionmentioning
confidence: 60%
“…Moreover, this percentage can be reduced further if the potential AGG grain has sub-boundaries. Experimentally, the sub-boundaries with very low misorientations of 0.04 and 0.09 inside Goss grains in Fe-3%Si steel was observed by Ushigami et al 25) Doner et al 26) also observed very small-angle grain boundaries with misorientation less than 1 within the primary recrystallized Goss grain. And also, Park et al 7) and Ko et al 27) reported the direct evidence of 3-dimensional wetting morphology at the growth front of Goss AGG from serial section images.…”
Section: Effect Of Grain-boundary Energy On Aggmentioning
confidence: 78%